Can Total Quality Management Improve Employee Performance? - Muhammad Naufal (BJRM (Bongaya Journal of Research in Management), 2021)
This study aims to determine how much influence Total Quality Management has on employee performance at PT. Teja Mukti Utama. Data collection using primary data obtained from employees of PT. Teja Mukti Utama was then used as respondents using a random sampling technique with a total sample of 75 r1espondents. The population is employees of PT. Teja Mukti Utama. Primary data collected through the distribution of the questionnaire have been tested using classical assumption tests in the form of normality assumptions, multicollonary assumptions, heteroscedasticity assumptions, and autocorrelation assumptions. Methods of data analysis using descriptive statistical analysis techniques. The results showed that Total Quality Management had a positive and significant effect on employee performance at PT. Teja Mukti Utama